Genomic analyses of the metastasis‐derived prostate cancer cell lines LNCaP, VCaP, and PC3‐AR. Issue 4 (24th December 2021) - Sienkiewicz, Karolina; Yang, Chunsong; Paschal, Bryce M.; Ratan, Aakrosh
Abstract: Background: The lymph node metastasis‐derived LNCaP, the bone metastasis‐derived PC3 (skull), and VCaP (vertebral) cell lines are widely used as preclinical models of human prostate cancer (CaP) and have been described in more than 19, 000 publications. Here, we report on short‐read whole‐genome sequencing and genomic analyses of LNCaP, VCaP, and PC3 cells stably transduced with WT AR (PC3‐AR). Methods: LNCaP, VCaP, and PC3‐AR cell lines were sequenced to an average depth of more than 30‐fold using Illumina short‐read sequencing. Using various computational methods, we identified and compared the single‐nucleotide variants, copy‐number profiles, and the structural variants observed in the three cell lines. Results: LNCaP cells are composed of multiple subpopulations, which results in nonintegral copy number states and a high mutational load when the data is analyzed in bulk. All three cell lines contain pathogenic mutations and homozygous deletions in genes involved in DNA mismatch repair, along with deleterious mutations in cell‐cycle, Wnt signaling, and other critical cellular processes. PC3‐AR cells have a truncating mutation in TP53 and do not express the p53 protein. The VCaP cells contain a homozygous gain‐of‐function mutation in TP53 (p.R248W) that promotes cancer invasion, metastasis, and progression and has also been observed in prostate adenocarcinomas. In addition, we detect the signatures of chromothripsis of the q arms of chromosome 5 in both PC3‐AR and VCaP cells, strengthening the association of TP53 inactivation with chromothripsis reported in other systems. Conclusions: Our work provides a resource for genetic, genomic, and biological studies employing these commonly‐used prostate cancer cell lines.